ANALISIS PENGARUH DAYA TARIK IKLAN DAN PROMOSI PENJUALAN TERHADAP KESADARAN MEREK DAN DAMPAKNYA PADA EKUITAS MEREK MIE SEDAAP DI KOTA SEMARANG - Elyardi, Aditya Helmi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2014)
This study aims to determine the extent to which the brand (brand) 'noodle Sedaap "can compete with its competitors to see the noodle as public awareness of the" noodles Sedaap "which is influenced by the variable variable Fascination Advertising and Sales Promotion. Some will find the criteria to examine how much influence these two variables on brand awareness certainly has an impact on brand awareness, brand equity is seen from the popularity and the public's ability to remember "Sedaap noodles". Criteria criteria ditinjolkan of variables including advertising Fascination: endorser attractiveness, attractiveness humor, plot, and appeal back sound or music system advertising. While the criteria of sales promotion variables include: the provision of free items, gifts, and procurement event. This study uses quantitative methods. Data were collected by questionnaire technique. Respondents for this study is the consumer of instant noodles in particular "Sedaap noodles" in Semarang with the number of respondents 96 people. Quantitative methods include the validity and reliability, the classic assumption test, testing hypotheses through F test, t test and the coefficient of determination (R2). The data analysis technique used is the linear regression analysis. The findings indicate that Fascination Advertising and Sales Promotion positive and significant impact on Brand Awareness, Brand Awareness in which the positive and significant impact on brand equity.